Brian Sutton-Smith memorial panel – a celebration of the life and works of Brian Sutton-Smith. Issue 1 (2nd January 2017) - Brown, Fraser; Beresin, Anna; Henricks, Tom; Meckley, Alice; Patte, Michael
ABSTRACT: On the final day of the 2015 TASP conference, we heard of the sad passing of our great friend and inspiration, Brian Sutton-Smith. The memorial panel, which was one of the centre-pieces of the 2016 TASP conference, was the first opportunity we had to mark his passing. We did so with a selection of memories and reflections on his life. Brian spent his adult life studying the phenomenon of play in all its forms: child and adult; frivolous and serious; sporting and educational; charming and disgusting. He showed that children are not always innocent in their play, and that adults often feel guilty about theirs. His academic legacy lies in hundreds of articles and over fifty books, including the seminal work The Ambiguity of Play (1997). However, those of us who knew him well also remember the great joy with which he lived his life. The Panel was a mixture of friends, collaborators, ex-students and TASP colleagues. All of them had a story to tell about the way this great supporter of TASP touched their lives.